DETERMINE LEVEL OF CONTROLLED MOVEMENT ACTIVITY AND LEVEL OF PHYSICAL FITNESS - Hamrolovov Rasul Abdusattorovich; Abdujalilova Kurvonoy (American Journals, 2023)
There are many simple and complex methods of determining physical work capacity. However, before using them, seeing a doctor and checking the state of health allows you to determine the level of physical fitness. Because ¬all methods of determining work capacity are related to the application of loads.
Keywords: Physical preparation , level of preparation, Determination of physical work capacity, Rufier-Dixon method, Harvard method, Number of repetitions of exercises , Group of large or small muscles involved in performing exercises, Speed of performing exercises, Amplitude of movements, Complexity of exercises, Muscle tension level and character, muscle power .